EMPOWERING SEBANI’S STREET CHILDREN THROUGH HIJAIYAH LITERACY AND PRAYER:: A Step Toward Religious Life - Dewi, Dewi Masita; M. Mahbubi (AlMurtado Journal of Social Innovation and Community Service, 2025)
Community Service Activity (PKM) with the title "Upgrading the Religiosity of Street Children in Sebani Village, Pasuruan City through Reading and Writing Hijaiyah Letters and Learning the Five Daily Prayers" has succeeded in providing a significant impact on increasing the religiosity of street children, both in terms of cognitive, affective, psychomotor, and social aspects. By using the Participatory Action Research (PAR) approach, this activity involves street children as active subjects who participate in the process of identifying problems, planning, implementing, and reflecting. Collaboration between researchers, communities, and participants creates a participatory and meaningful learning space. The use of various educational and Islamic theories strengthens the results of the activity: Transformative Islamic Theory encourages liberating and empowering spiritual changes. Al-Attas' theory emphasizes the importance of instilling manners and internalizing Islamic values. Maslow's theory provides an understanding of the importance of fulfilling basic needs as a foundation for the growth of spiritual awareness. Bandura's theory supports the social learning process through role models and positive reinforcement. Overall, this activity shows that increasing the religiosity of street children is not only possible, but can also be achieved effectively with the right, collaborative approach, and touching on spiritual aspects as well as their basic needs